Graphene‐Based Carbocatalysts for Thermoset Polymers and for Diastereoselective and Enantioselective Organic Synthesis. Issue 11 (24th April 2018) - Acocella, Maria Rosaria; Guerra, Gaetano
Abstract: This review reports on the catalytic activity of graphene oxide (GO) and high‐surface‐area graphite (HSAG) for some relevant organic reactions. It is shown that the main drawbacks of graphite‐based catalysts, that is, high catalyst loading and generally poor selectivity, can often be removed by operating under solvent‐free conditions. Moreover, some reactions that are catalyzed by GO as well as HSAG are presented. For these reactions, π stacking of the aromatic substrates with the graphitic planes plays a predominant role in the catalytic activity and the unexpected diastereoselective and enantioselective behaviors. Abstract : Carb‐loading : Herein, we report on the catalytic activity of graphene oxide (GO) and high‐surface‐area graphite (HSAG) for some relevant organic reactions. We show that the main drawbacks of graphite‐based catalysts, that is, high catalyst loading and generally poor selectivity, can often be removed by operating under solvent‐free conditions. Furthermore, the selectivity observed in reactions catalyzed by both GO and HSAG is explained.